2015
DOI: 10.1007/s00134-015-4062-0
|View full text |Cite
|
Sign up to set email alerts
|

Did studies on HFOV fail to improve ARDS survival because they did not decrease VILI? On the potential validity of a physiological concept enounced several decades ago

Abstract: High frequency oscillatory ventilation (HFOV) has been the subject of extensive physiological research for 30 years and even more so of an intense debate on its potential usefulness in the treatment of acute respiratory distress syndrome (ARDS). This technique has been enthusiastically promoted by some teams until two high-quality randomized clinical trials in adults with ARDS showed that HFOV did not decrease and might have even increased mortality. As a consequence of these results, physiological concepts su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 71 publications
0
22
0
2
Order By: Relevance
“…These results are disappointing for clinicians who have HFOV in their armamentarium for the management of moderate to severe acute respiratory distress syndrome (ARDS) in adults. However, as both trials possess the strength of being well-conducted prospective, randomized, controlled, multicenter, multinational studies, their results could be translated to general application in similar populations.Despite the theoretical advantage of less volutrauma and atelectrauma by the use of HFOV, there is growing evidence that ventilator-induced lung injury (VILI) still occurs due to continuous overdistension with high pressure, as well as oscillation amplitude and frequency related biotrauma [3]. Is the VILI the only responsible factor for the failure of HFOV?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are disappointing for clinicians who have HFOV in their armamentarium for the management of moderate to severe acute respiratory distress syndrome (ARDS) in adults. However, as both trials possess the strength of being well-conducted prospective, randomized, controlled, multicenter, multinational studies, their results could be translated to general application in similar populations.Despite the theoretical advantage of less volutrauma and atelectrauma by the use of HFOV, there is growing evidence that ventilator-induced lung injury (VILI) still occurs due to continuous overdistension with high pressure, as well as oscillation amplitude and frequency related biotrauma [3]. Is the VILI the only responsible factor for the failure of HFOV?…”
mentioning
confidence: 99%
“…Despite the theoretical advantage of less volutrauma and atelectrauma by the use of HFOV, there is growing evidence that ventilator-induced lung injury (VILI) still occurs due to continuous overdistension with high pressure, as well as oscillation amplitude and frequency related biotrauma [3]. Is the VILI the only responsible factor for the failure of HFOV?…”
mentioning
confidence: 99%
“…But with such critical elements respected and most unstable units held open, it seems reasonable that high-frequency oscillation (HFO), a strategy that targets reduced tidal volume and open lung, should be nearly ideal as a lungprotective methodology. It was therefore upsetting that a rigorously designed and executed clinical trial demonstrated that HFO could increase mortality risk [5].In this issue of Intensive Care Medicine, pioneering contributors to VILI research (Didier Dreyfuss and colleagues) present a cogent, detailed, and deliberately provocative argument that the cause of this unexpected result might be violation of the basic directive to avoid high airway pressures, with the likely mechanism being sustained and excessive tissue stretch [6]. The implication is that opening/closure and stress focusing, though acknowledged contributors to VILI at conventional ventilation frequencies, have received disproportionate attention.…”
mentioning
confidence: 99%
“…In this issue of Intensive Care Medicine, pioneering contributors to VILI research (Didier Dreyfuss and colleagues) present a cogent, detailed, and deliberately provocative argument that the cause of this unexpected result might be violation of the basic directive to avoid high airway pressures, with the likely mechanism being sustained and excessive tissue stretch [6]. The implication is that opening/closure and stress focusing, though acknowledged contributors to VILI at conventional ventilation frequencies, have received disproportionate attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation